Células mononucleares da medula óssea no tratamento da ruptura total dos tendões flexores e ligamento suspensor do boleto em equino - Yamada, Ana Lúcia Miluzzi [UNESP]; Oliveira, Patrícia Galvão Gomes de [UNESP]; Carvalho, Armando de Mattos [UNESP]; Watanabe, Marcos Jun [UNESP]; Hussni, Carlos Alberto [UNESP]; Alves, Ana Liz Garcia [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2011)
This paper describes the case of a horse treated in a Teaching Veterinary Hospital. The sutures of the flexor apparatus associated with cell therapy, the stem cell, provided a rapid response of repair compared to other cases treated in routine of the Hospital. The association of conventional treatments with the mononuclear fraction of bone marrow significantly contributed to the reduction of the hyperextension of the metatarsophalangeal joint. Ultrasound images showed rapid fill cell and decrease in inflammation.
Bone marrow mononuclear cells in the treatment of complete tear of flexor tendons and suspensory ligament in the horse
Keywords: equine; tendon; treatment; injury; mononuclear